Motivation of Cambodian and Thai international students in choosing Indonesia as a place to study the Arabic language - Maghfurin, Ahmad; Khotimah, Husnul; Wibowo, A. M; Naifah; Yani , Achmad (Journal of International Students, 2025)
This research explores why Cambodian and Thai students choose Indonesia to study Arabic, despite linguistically authentic Arab countries. Using narrative inquiry, data were collected through group discussions with eight international students studying in Indonesia for two years. Three main factors influenced their decision: quality Arabic programs, affordable education costs, and cultural similarities with shared Islamic values. Students found Indonesia’s contextual pedagogical approach more relevant to their culture than traditional Arab methods. Challenges included adapting to language differences, educational systems, and limited exposure to native Arabic speakers. To address these issues, the study recommends integrating modern learning technologies, enhancing teacher competencies, and creating immersion programs that connect students with native Arabic speakers in Indonesia. These insights aim to improve Arabic language education for international students and bolster Indonesia’s position as a hub for Islamic education in Southeast Asia.